Pentingnya Interaksi Sosial dengan Bermain terhadap Perkembangan Emosional Anak Usia Dini: The Importance of Social Interaction with Play on Early Childhood Emotional Development - Mukhlis (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2024)
Changes in the requirements for entering elementary school in Indonesia which require children to be able to read, write and count (calistung), and this policy has an impact on the social emotional development of early childhood. This study uses a qualitative approach with a literature study method by collecting data from related articles over the last ten years. Collect and analyze data sourced from books, newspapers and other scientific works. The results of the research show that play activities, such as multimedia games, animal characterization stories, role playing, congklak, and serial picture media, have a positive impact on children's emotional intelligence. This activity encourages children to interact socially, work together, and understand other people's feelings and perspectives. Apart from that, the role of parents in supporting children's emotional development is also very important. Suggestions for parents and teachers are to be more active in activities that support children's social and emotional interactions.